A critical assessment of questionable solar eclipse memories in the Byzantine Empire from the fourth to sixth centuries CE. (May 2023) - Murata, Koji; Hayakawa, Hisashi; Sôma, Mitsuru
This study analysed four records of questionable authenticity of total solar eclipses between the fourth and sixth centuries CE in Byzantine narrative sources. As it has been difficult to evaluate their credibility, they have not been utilised in modern astronomical studies. Three records originated in the fourth century, all of which have problems with accurate dating and provenance. The one remaining record concerns the total solar eclipse on 512 June 29. This study first reveals the problems with and questions around the reliability of all these records from astronomical perspectives based on the latest Δ T spline curve and recently proposed Δ T constraints. It then explores their philological and historical contexts to understand how and why these records were written.